Effeet of phospborus and zinc on yield, nutrient uptake and quantity of wheat (Triticum aestivum) - JAIN, N K; DAHAMA, A K (The Indian Journal of Agricultural Sciences, 2011)
A field trial was conducted for 2 consecutive winter (rabi) seasons of 2001-02 to 2002-03 to study the effect of phosphorus and zinc on yield, nutrient uptake and quality of wheat (Triticum aestivum L. emend. Fiori & Paol.) at Alwar (Rajasthan). Four levels of phosphorus (0, 30, 60 and 90 kg/ ha) and 5 levels of Zn (0.3, 6, 9 and 12 kg/ha) were applied along with the recommended doses of nitrogen and potassium. Results showed that phosphorus and zinc interaction had significant effect on grain, straw and biological yields, protein content, uptake of N, P, K and Zn, available phosphorus and zinc status after harvest of wheat. The mean maximum (4 907 kg/ha) and minimum (2 909 kg/ha) grain yield of wheat was recorded at P, Zn, and P,Zn, treatment combinations, respectively. Thus, for wheat a combined dose of 60 kg P,Oj + 6 kg Zn/ ha could be recommended for obtaining higher. productivity. However, optimum combined level of P and Zn was worked out to be 57.43 kg P,O, + 4.85 kg Zn/ha with an estimated yield of 4 495.65 kg/ha.